One-step growth of multilayer-graphene hollow nanospheres via the self-elimination of SiC nuclei templates. Issue 1 (December 2017) - Kim, Byeong; Nam, Deok-Hui; Jeong, Seong-Min; Lee, Myung-Hyun; Seo, Won-Seon; Choi, Soon-Mok
Abstract We introduce a one-step growth method for producing multilayer-graphene hollow nanospheres via a high-temperature chemical vapor deposition process using tetramethylsilane as an organic precursor. When the SiC nuclei were grown under an excess carbon atmosphere, they were surrounded via desorption of the hydrocarbon gas species, and graphene layers formed on the surface of the SiC nuclei via the rearrangement of solid carbon during the heating and cooling. The core SiC nuclei were spontaneously removed by the subsequent thermal decomposition, which also supplied the carbon for the graphene layers. Hence, multilayer-graphene hollow nanospheres were acquired via a one-step process, which was simply controlled by the growth temperature. In this growth process, the SiC nuclei acted as both the template and carbon source for the formation of multilayer-graphene hollow nanospheres.